The role of phosphatidylserine on the membrane in immunity and blood coagulation - Jiao Wang; Changxin Yu; Junyi Zhuang; Wenxin Qi; Jiawen Jiang; Xuanting Liu; Wanwei Zhao; Yiyang Cao; Hao Wu; Jingxuan Qi; Robert Chunhua Zhao (BMC, 2022)
Abstract The negatively charged aminophospholipid, phosphatidylserine (PtdSer), is located in the inner leaflet of the plasma membrane in normal cells, and may be exposed to the outer leaflet under some immune and blood coagulation processes. Meanwhile, Ptdser exposed to apoptotic cells can be recognized and eliminated by various immune cells, whereas on the surface of activated platelets Ptdser interacts with coagulation factors prompting enhanced production of thrombin which significantly facilitates blood coagulation. In the case where PtdSer fails in exposure or mistakenly occurs, there are occurrences of certain immunological and haematological diseases, such as the Scott syndrome and Systemic lupus erythematosus. Besides, viruses (e.g., Human Immunodeficiency Virus (HIV), Ebola virus (EBOV)) can invade host cells through binding the exposed PtdSer. Most recently, the Corona Virus Disease 2019 (COVID-19) has been similarly linked to PtdSer or its receptors. Therefore, it is essential to comprehensively understand PtdSer and its functional characteristics. Therefore, this review summarizes Ptdser, its eversion mechanism; interaction mechanism, particularly with its immune receptors and coagulation factors; recognition sites; and its function in immune and blood processes. This review illustrates the potential aspects for the underlying pathogenic mechanism of PtdSer-related diseases, and the discovery of new therapeutic strategies as well.